STUDY OF THE WELDING RESIDUAL STRESS INFLUENCE ON STABILITY OF SOLUTION OF NONLINEAR THIN RECTANGULAR PLATE - GAO YongYi; TANG Guo; WAN Wen; ZOU ShengHua (Jixie qiangdu)
According to theory of nonlinear vibration and Higher theory of plates and shells,the welding residual stress influence on stability of solution of nonlinear thin rectangular plate was studied to choose nonlinear rectangular thin plate possessed the welding residual stress as subject investigated. The conclusion which the stable and unstable regions of periodic solution of nonlinear rectangular thin plate possessed the welding residual stress has with the welding residual stress and change was gained. The conclusion which in different frequency ranges,the welding residual stress effects on stability of periodic solutions of different was obtained. The conclusion which the welding residual stress on the whole bring to reduce the stable region of periodic Solutions. The conclusion has certain guiding significance for the design of nonlinear rectangular thin plate possessed the welding residual stress.